Vita brevis : la carta de Floria Emilia a Aurelio Agustín - Gaarder, Jostein, 1952- (Tres edades. Biblioteca Gaarder, 2011)
A fictional letter to St. Augustine from his mistress, whom he repudiated in favor of celibacy. Prompted by her reading of his Confessions, the letter mixes nostalgic erotica with feminist criticism of the Church's position on women and love. The couple lived together for 10 years and had a son.